A comprehensive review of advances in thermoelectric generators: Novel materials and enhanced applications for sustainable transportation - Duc Tran Duy; Vinh Nguyen Duy; Nguyen Tien Tan; Vu Minh Dien; Pham Hoa Binh (International Journal of Thermofluids)
The energy crisis and related environmental issues due to the increasing power demand are the primary concerns in today's evolving globe. Modern energy conversion systems need dependability and scalability to overcome obstacles. This manuscript systematically examines recent research on high-performance thermoelectric materials, including novel alloys, nanostructured composites, and flexible materials designed to enhance energy conversion efficiency and adaptability across diverse environments. The literature selection spans peer-reviewed articles, patents, and emerging studies, emphasizing innovations in material properties, manufacturing methods, and design adaptations for transportation-specific challenges. In addition, this paper is organized to provide a dual perspective on both material innovation and practical integration in transportation systems, highlighting recent advancements in manufacturing processes and design. The unique structure of this review illuminates current limitations and prospective research pathways, offering insights for enhancing TEG performance and fostering sustainable, energy-efficient transportation technologies.